Fire - caribou - winter range relationships in northern Canada
We needed data on temporal changes in caribou forages after fire and relative use of age-classes of forests by caribou to help devise a fire suppression priority strategy for caribou winter range in north-central Canada. Consequently, from 1983 through 1986, we estimated the abundance of vegetation and relative use by caribou at 197 sites in western and eastern study areas on the winter range of the Beverly herd of caribou Rangifer tarandus). Species of lichens attained peak biomass at different periods after fire - as early as 40-60 years for Cladonia spp. to > 150 years for Cladina rangiferina and Cetraria nivalis. Biomass of the primary "caribou lichen", Cladina mitis, increased rapidly from 21-30 years after fire to 41-50 years and attained maximum biomass at 81-90 yeats in the west and 41-60 years in the east. However, total lichen biomass increased with age of forest to 100-150 years because biomass of Stereocaulon spp. did not peak until after 100 years. The biomass of "caribou lichens" Cladina spp. and Cetraria nivalis) stabilized after 61-80 years in the west and 41-60 years in the east. The biomass of terrestrial lichen species can be predicted from their cover. Caribou lichen abundance apparently was only one of several factors that caused caribou to use stands 151-250 years after fire more than othet age classes., number=2, journal=Rangifer, author=Thomas, D.C. and Barry, S.J. and Alaie, G., year=1996, month=Jan., pages=57–67